2004
DOI: 10.2308/iace.2004.19.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Using Games to Enhance Student Understanding of Professional and Ethical Responsibilities

Abstract: Given recent corporate scandals, the credibility of the accounting profession has been called into question. In order to restore public trust, accounting educators need to devise ways to convey the importance of ethics in our profession to our students. An alternative approach to using a traditional lecture to teach ethics is to use games. The purpose of this paper is to introduce a game strategy to teach ethics and professionalism to students. Using games makes learning more fun and also helps to maintain stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 4 publications
1
37
0
Order By: Relevance
“…Kuhn [12] summarises: ''class-room games accomplish both engagement and involvement in ways that are exceedingly helpful to business students'' engaging both emotion and reason. Haywood et al [13] cite psychological evidence that ''students learn and retain more of what they learn when they actively participate in problems''.…”
Section: Business Gamesmentioning
confidence: 98%
“…Kuhn [12] summarises: ''class-room games accomplish both engagement and involvement in ways that are exceedingly helpful to business students'' engaging both emotion and reason. Haywood et al [13] cite psychological evidence that ''students learn and retain more of what they learn when they actively participate in problems''.…”
Section: Business Gamesmentioning
confidence: 98%
“…Others have integrated the students' own experiences into teaching ethics (Hartog and Frame, 2004;Laditka and Houck, 2006); have had students write letters of complaints to companies about their ethical violations (Jurkiewicz et al, 2004); or have used classical literary sources (Coutu, 2006;Small, 2006) to teach ethics. Finally, one of the most engaging and effective pedagogies for teaching ethics, albeit also a challenging one for many faculty, is engaging students through experiential methods such as games, role plays, and behavioral simulations (e.g., Haywood et al, 2004;Thorne et al, 1999). It is important to note that regardless of which method is used, an indispensable element of an effective teaching/learning environment is for students to feel safe and supported to express their opinions (Fry and Kolb, 1979;Sims, 2004).…”
Section: Key Characteristics Of Best Practicesmentioning
confidence: 99%
“…Recent literature has indicated that today's generation of students seems to have a low threshold for boredom, as they thrive on action (Haywood et al 2004). Students born after 1980 (-Generation Y‖ or -Nexters‖) believe that they are entitled to an education and that their learning is all up to the teacher (Faust et al 2001).…”
Section: Implementation Guidancementioning
confidence: 99%
“…Analyzing and discussing relevant WSJ articles in class provide students and instructors an opportunity to grapple with accounting issues. Accounting students need to be challenged to use critical-thinking skills to see a situation from the viewpoint of all interested parties (Haywood et al 2004). This paper suggests that using the WSJ to discuss real-life applications of accounting information system not only improve student's understanding of AIS but also encourage them to be more actively involved in the learning process.…”
Section: Implementation Guidancementioning
confidence: 99%